Practice-led research, research-led practice and the dilemmas of ideation: an artistic inquiry - Kotze, Johannes Antonie (Vaal University of Technology, 2019)
This study explores two artistic methods of enquiry in order to firstly better understand the lived experience and its contributions on the formation of sexuality and secondly, to explore how a method can dissect and interrogate a theoretical discourse such as Queer theory. The project takes a twofold approach. In the Practice-led Research (PLR) section, which constitutes the first part, I attempt to utilize PLR as a means of exploring the lived experience along with the artistic contributions PLR might have on the ideation process and identity construction I made use of journal writings as a means for data generation and artistic exploration. The second part of this study, utilizing Research-led Practice (RLP), I attempt to dissect and interrogate Queer theory and the ideation process involved with RLP. I analyse Queer theory as a starting point for my artistic productions and explore and compared the two approaches to one another with regards to the ideation process and the construction of the self. The main aim of this study was to use the strategies of PLR and RLP to interrogate the process of ideation generation. The study set out to achieve three objectives. Firstly, it compares and contrasts the research methods suggested by PLR and RLP, as both operate from different points of ideation. Secondly it compares and contrasts the type of insights (philosophical ideations) around homosexuality and Queer theory that arose from using the two different methods. Lastly it tentatively/speculatively assesses which of the two approaches worked for me both as an artist (the making/ideation process) and as a gay man (the personal philosophical ideation process). In chapter one I discuss the background to the study and where it is situated within academia. In chapter two I discuss the two methodologies namely PLR and RLP and how I made use of them in the artmaking process. In chapter three I discuss the findings of working with PLR. In chapter four I engage with the theoretical discourse of Queer theory. In chapter five I discuss RLP and how Queer theory influenced the artmaking process. In chapter six I conclude with the findings. This study allowed me to channel my lived experience as a valid method of inquiry along with PLR. I discovered that a gay identity is based on personal experiences and shaped by the body. My second body of work (RLP) allowed me to investigate and interrogate Queer theory and I found that a Queer identity sits within a continuum. Working with these two methodological approaches allowed me to expand and grow as both an artist and gay man. Tentatively I conclude that PLR worked effectively for me to achieve this growth, whereas the RLP approach I found somewhat confining. Yet, the RLP approach ‘forced’ me to reconsider my preconceptions and the conclusions I had reached using the PLR approach.
M. Tech. (Partial Fulfillment) (Department of Visual Arts and Design: Fine Art, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Practice-led research; Research-led practice; Artistic inquiry; Dissertations, Academic -- South Africa.; Art -- Research.; Queer theory.; Body art.